A Planar low-cost full-polymer Optical Humidity Sensor. (2016) - Kelb, Christian; Körner, Martin; Prucker, Oswald; Rühe, Jürgen; Reithmeier, Eduard; Roth, Bernhard
Abstract: We present an all-polymer optical humidity sensor, based on a 1 mm plastic optical fiber (POF) with a U-bend, cladded with poly(N, N-dimethylacrylamide) (PDMAA) in the sensing region. The cladding changes its scattering properties on absorption of environmental humidity, thus modulating the transmitted optical power through the sensor. We explain the working principle of the sensor and show experimental results regarding scattering behavior of the cladding material and sensitivity to sudden humidity changes. We also propose a planar layout suitable for application to a hot embossing or lamination process for large-scale fabrication.